Note on Phalangopsidae crickets from Sabah and the Philippines, with description of a new species of Luzonogryllus - Tan, Ming Kai; Modina, Ris Menoel R.; Alo, Joanna Rose A.; Haibil, Helen H.; Mapi-Ot, Emmarie F.; Macas, Jessie Jay P.; Nuñeza, Olga Macas; Yap, Sheryl A.; Damit, Dayang Fazrinah Binti Awg; Japir, Razy; Chung, Arthur Y.c.; Robillard, Tony (Zootaxa, 2026)
Recent field work in Sabah state of Malaysia in Borneo, as well as Mindanao, Negros and Siquijor Islands in the Philippines has led to the collection of crickets from the family Phalangopsidae. This allows us to review the taxonomy of Luzonogryllus Yamasaki, 1978 from the Philippines and Sabah. We also describe a new species from Mindanao: Luzonogryllus (Apterozacla) appa Tan & Alo, sp. nov. We also present new locality records for Luzonogryllus (Apterozacla) mindoroensis Gorochov, 2006 in Negros and Siquijor Islands. Lastly, we also present new material of Strophiola lugubrina (Stål, 1877) from Mindanao and Negros Islands.